2017
DOI: 10.1186/s12911-017-0576-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors associated with the uneven utilization of telemedicine in Norway: a mixed methods study

Abstract: BackgroundNorway has a long history of using telemedicine, especially for geographical reasons. Despite the availability of promising telemedicine applications and the implementation of national initiatives and policies, the sustainability and scaling-up of telemedicine in the health system is still far from accomplished. The main objective of this study was to explore and identify the multi-level (micro, meso and macro) factors affecting telemedicine utilization in Norway.MethodsWe used a mixed methods approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 45 publications
5
74
0
7
Order By: Relevance
“…The observation that higher satisfaction with the quality of telemedicine care was associated with urban location is compatible with a study in Norway that showed small hospitals are less likely to use telemedicine because it decreases the need for physical presence of clinicians, and might lead to difficulties with recruitment and retention of clinicians to rural sites. 25 The American Medical Association Physician Benchmark Survey found that the financial burden of implementing telemedicine may be a barrier for small practices. 26…”
Section: Discussionmentioning
confidence: 99%
“…The observation that higher satisfaction with the quality of telemedicine care was associated with urban location is compatible with a study in Norway that showed small hospitals are less likely to use telemedicine because it decreases the need for physical presence of clinicians, and might lead to difficulties with recruitment and retention of clinicians to rural sites. 25 The American Medical Association Physician Benchmark Survey found that the financial burden of implementing telemedicine may be a barrier for small practices. 26…”
Section: Discussionmentioning
confidence: 99%
“…The use of information and communication technology (ICT) has a long history [ 10 ]. Although ICT like VC are more commonly used in surgical treatment, there are few studies on the use of VC as a tool in primary cancer care [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organisational case studies have shown that introducing video consultations is a complex change that disrupts long established processes and routines 891011. Some clinicians express concerns about technical and clinical quality, privacy, safety, and accountability (for example, in relation to litigation if something goes wrong) 91011. Whether justified or not, these reservations can be a major barrier to expanded use.…”
mentioning
confidence: 99%